Analisis Sistem Informasi Eksekutif Dalam Layanan Listrik Kantor Pelayanan Dan Unit Listrik Desa PT. PLN (Persero) Unit Induk Wilayah Kalimantan Selatan Dan Kalimantan Tengah - Habibi, Afrizal; Yunita, Helda; Samsuri (Journal Information Technology Trends (JITRENDS), 2023)
Customer service data in the service office and village electricity unit not managed properly because the system is currently used is limited to units on urban area only. Therefore a new system was built that could be used to manage electricity customer service data. In order to support this research, the method of data collection is carried out by means of interviews, library studies, analysis, system design, system building, testing and system implementation. This system makes it easy to manage customer electricity service data at the Village Service Office and Electric Unit and make it easier for Commerce Deputy Mechanism Managers and Revenue Assurance to monitor data for the purpose of executing customer service improvements in villages or sub-districts throughout South Kalimantan and Central Kalimantan.